A Study of Technology-Integrated Approaches for Facilitating English Language Learning among University Students: A Conceptual Analysis - Pandya, Payal B.; Raval, Jayeshkumar Vasudev (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
With the rapid advances of digital technology, English language learning at universities is increasingly through tech-based that promotes interactive, autonomous and collaborative learning. This conceptual paper studies various technology-enhanced approaches. These include computer-assisted language learning (CALL), learning through mobile, captioned media, telecollaboration & robot-assisted language instruction. The study analyzes their effect on learners’ linguistic competence, autonomy and multimodal engagement. Based on newer empirical and conceptual studies, the paper discusses how technology can enhance the development of language skills, boost learner motivation and provide opportunities for intercultural communication. It also identifies challenges around teachers’ preparedness, instructional designs, institutional support, and learners’ digital literacy. The results reveal technology is not just an addition but a pedagogically transformative factor in higher education. In conclusion, to be effectively integrated, there needs to be planning, training, and access. At the university level, this conceptual analysis offers pedagogical implications and directions for further research on sustainable technology-enhanced English language teaching practices.